Dynamic panel model of dividend policies: Malaysian perspective - Shafai, Nor Anis; Md Nassir, Annuar; Kamarudin, Fakarudin; Abdul Rahim, Norhuda; Ahmad, Nor Hayati (Faculty of Management and Finance, University of Finance and Management in Warsaw, 2019)
The aim of this paper is to identify the key determinants of the dividend policies for Malaysian listed firms. The sample in this study incorporates the top 100 listed firms on Bursa Malaysia (Bursa) over a ten-year period from 2007 to 2016. The dynamic panel data set was constructed using the sample firms. The results indicate that dividend policies are positively significantly related to profitability and firm size in Malaysia. Thus, this suggests that Malaysian listed firms determine their future dividends based on past dividend payments. Meanwhile, dividend policies are negatively and significantly associated with leverage and business risk. Therefore, this study used the generalized method of moments (GMM) to reveal unique findings and the findings should inspire analysts, policy makers, institutional investors and investors to examine the dividend policy puzzle, especially for developing countries.